2007
DOI: 10.1086/522012
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐Transcriptome Analysis ofPlasmodium falciparumField Isolates: Identification of New Pathogenicity Factors

Abstract: This is the first attempt to identify genes involved in parasite pathogenic mechanisms against human ECs. The finding of PALPFs illuminates perspectives for novel therapeutic strategies against cerebral complications of malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…One way to approach the analysis of parasite-specific factors in disease severity is to compare the transcriptional profiles of parasites taken directly from patients with different clinical presentations. Several such analyses have already been carried out but with conflicting conclusions (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…One way to approach the analysis of parasite-specific factors in disease severity is to compare the transcriptional profiles of parasites taken directly from patients with different clinical presentations. Several such analyses have already been carried out but with conflicting conclusions (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…The applicability of RNA interference (RNAi), which has been extremely important in elucidating gene function in several eukaryotic organisms, is still being debated. Several groups have reported successfully using double-stranded RNA to specifically knock down target genes such as falcipains-1 and 2 (6, 7), dihydroorotate dehydrogenase (8), PfMyb1, a transcription factor (9), and several genes putatively involved in parasite infected RBC induction of endothelial cell apoptosis (10). However, whether this is mediated via RNAi per se or anti-sense mechanisms remains unclear, especially in light of bioinformatics data suggesting that key conserved components of the RNAi machinery are not encoded in the P. falciparum genome (11,12).…”
mentioning
confidence: 99%
“…Optical density (OD) was read with a Stat FaxH 3200 (Fisher Bioblock Scientific, Illkirch France) at 405 nm, with a reference filter of 492 nm. The mean OD of pRBC-activated HLEC and hCMEC/D3 to RBC-activated HLEC and hCMEC/D3 and mean OD of 3D7-activated HLEC and hCMEC/D3 to RBC-activated HLEC and hCMEC/D3 was calculated, using a positivity cut-off of 3, as recommended [6, 14]. …”
Section: Methodsmentioning
confidence: 99%
“…Using cocultured human lung EC (HLEC) and pRBC field isolates from Gabon, we showed that although almost all isolates provoked cytoadherence, only a few triggered apoptosis (via cytoadherence or diffusible factors), and that these isolates tended to have been drawn from patients with neurological disorders [9]. The potential of pRBC to trigger HLEC apoptosis varies according to the isolate, and is associated to the expression of Plasmodium apoptosis-linked pathogenicity factors (PALPFs) [9, 14, 15]. Human endothelial cells in different tissues may not all express the same surface receptors [16], and this could explain some functional differences.…”
Section: Introductionmentioning
confidence: 99%